Transformation of Pension Systems in the Countries of Eurasian Economic Union - Dyatlov, Sergey Aleksandrovich; Feygin, Grigory Feliksovich; Lebedeva, Lyudmila Fedorovna (Economy of Regions, 2017)
Current integration processes, develop actively on the territory of Eurasian Economic Union (EEU). A single labour market has been created. Building a model of social interaction between the State Parties of EEU is crucial for the development of longterm strategy of the EEU. The Treaty on the Eurasian Economic Union (2014) provides identifying factors, threats and potential areas of cooperation between the EEU countries in the sphere of pension services. This identification requires systematizing the key indicators of EEU national pension systems. There is a necessity to improve not only the pension system of every country individually but also to search the possibilities for their coordination in the future. From the beginning of 1990th, in all EEU countries, the pension systems have been establishing and developing. The authors present the brief review and comparative analysis of these systems. We identify their similarities and differences according to set criteria and determine possible areas for integration of pension systems in EEU. We consider both the socio-economic parameters (including retirement age, amount of pension payments, pension payment procedures and pattern of pension payments) and the demographic features of the EEU countries. The paper systematizes the macroeconomic and population indicators. On their basis, we reveal the opportunities and risks for the EEU countries cooperation in the sphere of pension system. To investigate the pension systems of EEU countries, we applied the methods of logical, comparative and statistical analysis. The results of this study indicate that the coordination of the pension systems of EEU countries needs cooperation in four directions. First of all, it is necessary to elaborate the single principles of social guarantees for retirees. Secondly, there is a need to ensure guaranteed retirement income. Thirdly, single basic approaches for the regulation of investment activities of pension funds should be elaborated. Last, single data bank for pension provision can be created.